Zakat literacy index in Aceh - Ana Fitria,; Rina Desiana,; Azimah Dianah,; Muhammad Rizki, (Indonesian Journal of Islamic Economics Research, 2024)
To enhance zakat collection, a policy based on community literacy about zakat is necessary. This research aims to evaluate the fundamental and advanced knowledge of zakat among Aceh Province residents, serving as a foundation for economic growth post-Covid-19. The study utilizes the Zakat Literacy Index technique, employing a quantitative descriptive approach to assess the zakat literacy level of Muslim communities in Indonesia. By employing the zakat literacy indexation model developed by Saoqi et al. (2019), the study provides a comprehensive description of zakat literacy in Muslim communities, particularly in Aceh Province. The findings will facilitate the evaluation of poverty alleviation strategies and inform policies for increasing zakat literacy and empowering the economy to address poverty issues in Indonesia. This research can influence government regulations on improving zakat collection, specifically in Aceh Province